A spotlight on fossil fuel lobby and energy transition possibilities in emerging oil-producing economies - Isaac Ankrah; Michael Appiah-Kubi; Eric Ofosu Antwi; Ivy Drafor Amenyah; Mohammed Musah; Frank Gyimah Sackey; Richard Asravor; Isaiah Sikayena (Heliyon)
This study investigates the impact of fossil fuel industry on renewable energy deployment in emerging oil-producing economies, using Ghana as the subject of analysis. Drawing on the “theory of lobby,” the study extends previous analyses to examine how fossil fuel production influences the possibility of transitioning to renewable energy. The results, based on a stepwise estimation technique, within a two-regime Markov-switching Model, show a consistent negative relationship between fossil fuel production and renewable energy deployment, supporting the lobby effect theory in Ghana's energy economy. Notably, while fossil fuel production initially increases the probability of transitioning to renewable energy (from 39.65 % to 58.42 %), this trend is reversed by foreign direct investment, reducing the likelihood to approximately 42 %. These findings underscore the need to expand the lobby-effect theory to include indirect economic influences, such as investment patterns and structural dependencies, that enable fossil fuel dominance. Through its focus on Ghana, this study contributes fresh insights into the energy transition dynamics of emerging economies, offering a broader and more inclusive perspective to the energy transition literature.